2013
DOI: 10.1063/1.4836095
|View full text |Cite
|
Sign up to set email alerts
|

Field nano-localization of gas bubble production from water electrolysis

Abstract: Using a tip shaped electrode and ac voltages, we show that the production of micro bubbles of gas from water electrolysis is localized at the tip apex inside a domain in the voltage frequency phase space. A model taking into account the electrode shape and dimensions explains these results which suggest a field effect control of the electrolysis reaction rate at a nanometer scale.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 31 publications
(28 reference statements)
1
29
0
Order By: Relevance
“…Owing to their high stability and spontaneous formation, surface NBs are important in the context of many modern applications where the role of surface interactions becomes relevant [36,37], such as separation processes [38]. Surface NBs have been also found to play a significant role in the case of flotation [39], drag reduction [40,41], nanocomposite foams [42,43], nanomaterial engineering [44], catalysis and electrolysis [45], plasmonic and vapour NBs [46], and transport in nanofluidic devices as well as boiling heat transfer by serving as nucleation sites [47]. The fabrication of nanoporous polypyrrole (PPy) films is a specific example, where stable NBs can be used as a template to create nanoporous films [48].…”
Section: Introductionmentioning
confidence: 99%
“…Owing to their high stability and spontaneous formation, surface NBs are important in the context of many modern applications where the role of surface interactions becomes relevant [36,37], such as separation processes [38]. Surface NBs have been also found to play a significant role in the case of flotation [39], drag reduction [40,41], nanocomposite foams [42,43], nanomaterial engineering [44], catalysis and electrolysis [45], plasmonic and vapour NBs [46], and transport in nanofluidic devices as well as boiling heat transfer by serving as nucleation sites [47]. The fabrication of nanoporous polypyrrole (PPy) films is a specific example, where stable NBs can be used as a template to create nanoporous films [48].…”
Section: Introductionmentioning
confidence: 99%
“…All the experiments are monitored using a highspeed camera (photron SA3). When the ultrasonic transducer is not excited, the bubble generation can be compared to that obtained in the study reported by Hammadi et al 19 in the case of controlled electrolyte. Indeed, we also observe that for a fixed frequency, a voltage threshold should be reached before the bubble generation starts (Fig.2).…”
Section: © 2017 Author(s) All Article Content Except Where Otherwismentioning
confidence: 99%
“…13). The electrical field induces high current density inside the solution close to the region of high curvature [14]. The resulting flux accumulates molecules at a precise point in the vicinity of the tip apex [15] and the concentration gradient in solution tends to be counteracted by convection.…”
Section: Electrical Field and Confinement By Gelmentioning
confidence: 99%
“…5, our kinetic data are in good agreement with the data of Galkin and Vekilov [21][22] obtained for the same NaCl concentration at 12.6°C, using droplets of 1µL suspended in Teflon wells. Moreover, the supersaturation range experimentally accessible when reducing the volume of nucleation to the nL-pL range is increased for kinetic [5] and thermodynamic [14] reasons (see part 3.2. ).…”
Section: -Microfluidic Devices: (I) Molded In Pdms and Adapted From Smentioning
confidence: 99%
See 1 more Smart Citation